Antibiotic contamination of fresh organic fertilizers and processed bio‐based fertilizer products - Sophia Albert; Elke Bloem (Agrosystems, Geosciences & Environment)
Abstract Fertilizer prices have risen considerably in recent years, making the use of nutrient‐rich organic side streams as a fertilizer more attractive. However, the use of such materials bears certain risks such as the introduction of unwanted pollutants, germs, or unbalanced nutrients into the environment. Antibiotics are a group of drugs used in large quantities in humans and animals and are therefore often found in organic waste streams that are used as fertilizers. Only a small proportion of the administered dose is absorbed and metabolized, while the significant part is excreted metabolized or unchanged and can remain in an active form. This study identified 14 antibiotics from the classes of tetracyclines (TCs), fluoroquinolones (FQs) and sulphonamides (SAs) in bio‐based fertilizers (BBF) and discussed the effects of processing on residual concentrations. High levels of antibiotics were detected in manure, sewage sludge, and digestate. Composting in an extensive composting plant as one processing possibility had the potential to reduce TCs by 26% and FQs by 37% when sewage sludge with green waste was treated. Less antibiotic residues were detected in struvite and animal‐based by‐products. In addition, the nutrient concentration in processed BBF is often high, which means that lower amounts of fertilizer are used in agricultural systems. The low levels also mean that few antibiotics are spread.